Children’s toys from the perspective of parents and preschool teachers - Colić, Vesna Đ.; Milošević, Tamara M.; Colić, Uglješa D. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2019)
The research relates to the attitudes of parents and preschool teachers towards children’s toys, from the perspective of family and institutional context.  The aim of the research is to examine the opinions of parents and teachers about the usefulness of toys, their influence on the formation of stereotypes in children, as well as the influence of the market, TV advertisements and other factors on the selection and purchase of toys. The research sample is suitable and consists of 105 preschool teachers and 105 parents of preschool children from preschools in Novi Sad. The method of voluntary anonymous surveys was applied, and the questionnaire was taken from B. Sutton-Smith and somewhat modified and adapted. The results were subjected to descriptive statistics. The obtained results indicate that the opinions of parents and preschool teachers are similar with regard to the contribution of toys to the education of children and the development of their imagination, the safety of toys and the disapproval of toy weapons. Most preschool teachers do not approve of toys advertising, while most parents approve of it. Space is also a problem and influences the choice of children’s toys in preschools, while parents’ opinions on this issue are divided. The purchase of toys in preschools is usually decided by adult professionals, sometimes parents are consulted, and very rarely children are consulted. In the family, children together with adults most often decide on the purchase of toys, then the children themselves and rarely the adults alone. The authors of this research believe that the obtained results point to the need to make all adults significant to the child more aware of the importance of their role and responsibility for the selection of toys and the messages they send to children daily through toys.
Keywords: context; toys; preschool teachers; PARENTS; children